DEMOCRATIC LEADERSHIP OF QUALITY-BASED PRINCIPALS IN PUBLIC JUNIOR HIGH SCHOOL IN MERAUKE REGENCY - Tethool, Evie Susanna; Diat Prasojo , Lantip (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Democracy in Indonesia faces problems such as the disruption of freedom of expression in criticizing the government, physical violence committed by a junior high school principal against a teacher in Jombang Regency, East Java. Principals who are far from democratic values such as deliberation or expressing opinions, Public Junior High Schools in Merauke are less able to control subordinates. This study aims to analyze the implementation of quality-based democratic leadership by Public Junior High School principals in Merauke Regency and identify supporting and inhibiting factors. The method used in this study is a qualitative descriptive approach with primary data sources in the form of in-depth interviews, direct observation, and documentation in five Public Junior High Schools in Merauke, as well as secondary data in the form of archives and educational regulations. The results show that a quality-based democratic leadership style can create a collaborative work climate that improves teacher performance and the quality of educational services, if balanced with effective coordination, continuous motivation, and transparency in decision-making. However, obstacles were also found in the form of a lack of firmness of leaders in enforcing discipline, weak consistency in providing examples, and the influence of local culture that gives rise to personal sentiments. Supporting factors include active teacher involvement in school program planning, support from local government policies, and school accreditation that encourages quality improvement. The conclusion of this study is that democratic leadership of quality-oriented school principals is effectively implemented if accompanied by increased managerial competence, strengthening the role of the school principal as a motivator, and a commitment to transparency and professionalism.